2015
DOI: 10.1177/0022042615616431
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Withdrawal, Posttreatment Abstinence, and Days to First Cannabis Use Among Emerging Adults in Substance Use Treatment

Abstract: Very little prospective research investigates how cannabis withdrawal is associated with treatment outcomes, and this work has not used the Diagnostic and Statistical Manual of Mental Disorders (5th ed.; DSM-5) thresholds for cannabis withdrawal. The sample included 110 emerging adults entering outpatient substance use treatment who were heavy cannabis users with no other drug use and limited alcohol use. We used survival analyses to predict days to first use of cannabis and logistic regression to predict whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 90 publications
(155 reference statements)
0
35
0
Order By: Relevance
“…In a separate sample of 110 treatment-seeking emerging adults who were heavy cannabis users, those with significant cannabis withdrawal had a 53% greater risk of earlier resumption of cannabis use than those who did not report significant withdrawal symptoms 28 .…”
Section: Introductionmentioning
confidence: 92%
“…In a separate sample of 110 treatment-seeking emerging adults who were heavy cannabis users, those with significant cannabis withdrawal had a 53% greater risk of earlier resumption of cannabis use than those who did not report significant withdrawal symptoms 28 .…”
Section: Introductionmentioning
confidence: 92%
“…The importance of the treatment of CWS on the maintenance of cannabis use or substance use trajectories over time is unclear and awaits further study. From previous literature, there is small evidence for both 1) CWS treatment initiated abstinence or dose reduction12,13 and 2) CWS treatment does not influence cannabis use in the following 18,20,42,109. Frequent cannabis users had reported that withdrawal symptoms negatively influence their desire and ability to quit 12,13,18,105.…”
Section: Impact On Cud or Dependencementioning
confidence: 99%
“…Outpatient treatment programs improved the psychosocial functioning and dropped the cannabis use for a while 12,13. Currently, only a few long-term follow-ups are available, so far showing no sustaining improvement of CUD subsequent to outpatient detoxification attempts 18,20,42,109…”
Section: Impact On Cud or Dependencementioning
confidence: 99%
“…At the time of writing, cannabis withdrawal has been investigated in adolescent samples [30, 31], emerging adults [32], adult long-term, daily cannabis users [5, 22], and environments that include closed residential research units [27, 28, 33], outpatient settings [25, 26, 34], and within the context of clinical studies evaluating behavioral and pharmacological interventions for the treatment of cannabis use disorder [9, 10, 11, 13, 35]. …”
Section: Characteristics Of the Cannabis Withdrawal Syndromementioning
confidence: 99%